Economically important underutilized fruits suitable for arid eco-system-A review (IASH Indian Journal of Arid Horticulture, 2025)
The climatic conditions of western Rajasthan and parts of Gujarat are characterized by low and erratic rainfall, high thermal oscillation, and harsh weather. As a result, much of the land is barren, making it suitable for the cultivation of arid fruits that are currently underutilized. Some examples of these underutilized fruits include Kair (Capparis deciduas L.), Karonda (Carissa carandas L.), Khejri (Prosopis cineraria), Pilu (Salvadora oleoides), Tamarind (Tamarindus indica), Wood apple (Feronia limonia L. Swingle), Cactus pear (Opuntia ficus-indica), Nagphani (Opuntia elatior Mill.), and Dansara (Rhusmysorenis Heneex Wight & Arn.). These fruit crops grow naturally and have been utilized by local communities for a long time due to their nutritional value and resilience to harsh climatic conditions. This review focuses on the underexploit ed fruits with the potential to thrive in such environments, discussing aspects such as value addition, post-harvest management, and future prospects for these crops.